Key Kombucha Process Parameters for Optimal Bioactive Compounds and Flavor Quality - Saikiran Chaluvadi; Arland T. Hotchkiss; Benjamin Smith; Bianca McVaugh; Andre K. White; Giselle K. P. Guron; John A. Renye; Kit L. Yam (Fermentation)
The relationship between Kombucha fermentation process parameters and microbial composition was investigated. Green tea Kombucha fermented slower, producing a higher sugar/acid ratio, residual sucrose, and sweeter taste compared to black tea Kombucha. No known probiotic bacteria were identified in Kombucha since Zygosaccharomyces, Brettanomyces, Komagataeibacter, and Gluconacetobacter were the dominant genera observed based on 16s rRNA sequencing analysis. Green tea epigallocatechin and epigallocatechin gallate inhibited bacterial growth in black tea Kombucha broth in a concentration-dependent manner. Green tea Kombucha produced from a 10-day inoculum had a higher sugar/acid ratio, residual sucrose, acetic acid, gluconic acid, and a pleasant flavor compared to a 15-day inoculum. In blended green and black tea Kombucha, a solid bacterial pellicle 9-day inoculum increased the amounts of glucose, fructose, acetic acid, gluconic acid, and ethanol, yet there was a lower sugar/acid ratio and residual sucrose, but no change in the catechin profile, compared to a completely liquid inoculum. Increasing the surface area/volume ratio to 0.16 during Kombucha production increased levels of glucose, fructose, and gluconic acid, while acetic acid and ethanol levels remained the same by favoring aerobic vs. anaerobic fermentation. These Kombucha fermentation process parameter results will help producers devise strategies for better quality control.